Challenges in the implementation of responsible research and innovation across Horizon 2020. Issue 3 (2nd September 2022) - Tabarés, Raúl; Loeber, Anne; Nieminen, Mika; Bernstein, Michael J.; Griessler, Erich; Blok, Vincent; Cohen, Joshua; Hönigmayer, Helmut; Wunderle, Ulrike; Frankus, Elisabeth
ABSTRACT : In the last decade, the European Commission (EC) developed an ambitious strategy to promote RRI across the Horizon 2020 Framework Programme for Research and Innovation (H2020). This effort resulted in a significant number of European-funded projects that substantially expanded the available knowledge of the theory, methods and implementation of RRI. However, various evaluations and studies revealed a limited and diffuse implementation of the concept. In this article, we aim to shed some light on this matter with a study covering eight programme lines of H2020 (ERC, MSCA, LEIT, FOOD, ENV, SEC, WIDENING and EURATOM). We employ an extensive policy document analysis and 112 semi-structured interviews carried out with various stakeholders. We argue that the limited implementation of RRI in H2020 is the result of conflicts with existing values, science cultures, economic objectives, restricted resources for its implementation and a lack of clarification around what RRI means.